Carl Schurz Vrooman papers - Vrooman, Carl Schurz, 1872-1966.; Scott, Julia Green, 1839-1923.; Vrooman, Frank Buffington, 1862-1951.; Vrooman, Hiram, 1871-; Vrooman, Julia Scott; Vrooman, Walter, 1869-
Correspondence, diaries, speeches, writings, and other papers of Vrooman and Scott family members, chiefly Vrooman; his wife, Julia Scott Vrooman; his mother-in-law, Julia Green Scott; and his brothers, Frank Buffington Vrooman, Hiram Vrooman, and Walter Vrooman. Subjects include agriculture and agricultural policy, especially during Vrooman's tenure as assistant secretary of agriculture in the Woodrow Wilson presidential administration; social life in Washington, D.C., in the early twentieth century; and Vrooman's interest in religion and spirituality. Includes material pertaining to Carl G. Bickel and the Farmers' Political Conference of Illinois; the poet Vachel Lindsay; the founding of Ruskin Hall, Oxford; a deposition of Carl Schurz Vrooman in a case concerning the Scott-Lees Collegiate Institute, Jackson, Ky.; and the "Wisconsin matter" of 1917 in which Vrooman questioned the wartime loyalty and leadership of the University of Wisconsin.
Vrooman's correspondents include Louis Dembitz Brandeis, William Jennings Bryan, Paul H. Douglas, Warren G. Harding, Herbert Hoover, Edward Mandell House, Reinhold Niebuhr, and Franklin D. Roosevelt. Correspondents of Julia Scott Vrooman include Mary Baird Bryan, Vachel Lindsay, Eleanor Roosevelt, Adlai E. Stevenson (1900-1965), and Edith Bolling Galt Wilson.
Farmer, publicist, and U.S. assistant secretary of agriculture.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bickel, Carl G; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Bryan, Mary Baird, -- 1861-1930 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Douglas, Paul H. -- 1892-1976 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Lindsay, Vachel, -- 1879-1931.; Lindsay, Vachel, -- 1879-1931 -- Correspondence; Niebuhr, Reinhold, -- 1892-1971 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Stevenson, Adlai E. -- 1900-1965 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Scott family; Vrooman family; United States. -- Department of Agriculture; Farmers' Political Conference of Illinois; Ruskin Hall, Oxford; Scott-Lees Collegiate Institute; University of Wisconsin; Agriculture -- United States; Agriculture and state -- United States; Patriotism; Religion; Spirituality; World War, 1914-1918 -- United States; Washington (D.C.) -- Social life and customs; Farmers; Publicists; Public officials